FORAMINIFERA EVOLUTION AND DISPERSAL IN THE EARLY PALEOGENE POSTCRISIS EPOCH - Bugrova E.M. (My University, 1999)
Data on changes in the taxonomic composition of planktonic and benthic foraminifers across the Cretaceous-Paleogene boundary are presented. Extinction events in the highly specialized planktonic group were most remarkable. The new diversification stage began in the Danian starting with the appearance of primitive new-comers. The diversification went trough several phases before zonal boundaries became apparent. The extinction of benthic forms was of various character depending on the state of evolutionary development and on the facies confinement of their populations. Mass extinction occurred among the specialized forms that inhabited shallow shelf areas. The taxonomic diversity of more deep-water and genetically primitive groups decreased to a lesser extent. The revised stratigraphic and geographical ranges of some genera are presented along with examples illustrating the origin of new lineages and the progressive development of certain groups against the background of the degrading of others. The role of immigrant species in the regional assemblages is also elucidated.
Keywords: Paleogene; Cenozoic::Paleogene; Кайнозой::Палеоген